EFEKTIFITAS PELAKSANAAN ALOKASI DANA DESA BERDASARKAN PERMENDAGRI NO 113 TAHUN 2014 TENTANG PENGELOLAAN KEUANGAN DESA - L. M. Ricard Zeldi Putra (Lembaga Penelitian dan Pengabdian Masyarakat, 2017)
The Organization of the Government of the village of terpisakan no peyelenggaraan autonomous region. Through law No. 6 Year 2014 about villages, each village given discretion to set its own kewenanganya, either the authority based on the origin of the local scale, the powers and authority of the village, in the transferred by the Central Government/provinces//kota in accordance with government legislation. This research uses the normative-empirical type. The data used in this research is the primary data, namely data obtained directly from the field in the form of interviews and questionnaires and secondary data, namely data obtained from graphical documents (tables, notes, meeting, meetings, etc), photographs, films, video recordings, and other things that can enrich the primary data. Research results show that implementation of the allocation of Funds in the village of Banabungi Village have been implemented but in pelaksanaanya is not effective. It is based on is Not dilaksanakanya the principle of transparency and participatory in its own ruling, a factor pelaksanaanya i.e. the absence of legal sanctions or force power for the Government when the village does not implement legal norms. While the position of Permendagri NO. 113 Year 2014 about financial management is in compliance as regulations, although the above provision does not mention explicitly the type of legislation in the form of a regulation of the Minister, but the phrase rules set by Ministers at the top, reflecting the existence of ministerial regulation as one of the types of legislation.